2012
DOI: 10.1080/09581596.2012.710738
|View full text |Cite
|
Sign up to set email alerts
|

Complaints about dog faeces as a symbolic representation of incivility in London, UK: a qualitative study

Abstract: During a ‘Well London’ study, residents were asked about their neighbourhood and its environment. Above all other complaints, ‘dog poo’ was mentioned as a key concern. Despite low rates of infection and disease among the human population resulting from contact with canine faecal matter, the concerns of the public continue to rate it as a serious public health issue. Most public health studies, therefore, seek to identify processes of transmission and disease pathology as a method of addressing the problem. Thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(31 citation statements)
references
References 5 publications
2
29
0
Order By: Relevance
“…Differences in how our relatively homogenous sample of white middle-class participants described the role of their dogs in daily life are suggestive of considerable heterogeneity in the ways that dog-ownership is practiced, given that neighbourhood characteristics, ethnicity and socioeconomic status appear to influence who derives benefit from the presence of dogs in urban settings (McCormack et al, 2010;Derges et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Differences in how our relatively homogenous sample of white middle-class participants described the role of their dogs in daily life are suggestive of considerable heterogeneity in the ways that dog-ownership is practiced, given that neighbourhood characteristics, ethnicity and socioeconomic status appear to influence who derives benefit from the presence of dogs in urban settings (McCormack et al, 2010;Derges et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…This is attributable to unattended dogs and litter from dog feces, affecting some dog owners as well as non-owners, particularly women and older adults (McCormack et al, 2010;Toohey & Rock 2011). The symbolic importance of dog-waste, furthermore, was a salient finding in qualitative research with residents of disadvantaged neighbourhoods (Derges et al, 2012). Studies of policies on dog-ownership in cities also point to simmering tensions and overt conflicts concerning which people gain access to and exert influence over public space (Brandow, 2008;Walsh, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…While not measured directly, other characteristics such as dog-waste in public areas may make some locations less aesthetically appealing and could deter dog-walking as well as other types of physical activities. 27 Previously, we found that regardless of dog-ownership, adults who perceived their neighbourhood as highly aesthetically pleasing were more likely than those perceiving low aesthetics to participate in any neighbourhood recreational walking. 20 Hence, specific built characteristics might provide more support for some types of physical activities than other types, and some built characteristics might be more or less important than other characteristics during an individual's attempts to initiate or maintain physical activity.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, dog-related nuisances as well as outright threats deter physical activity and fuel animosity to an extent that is relevant for equity in public health (Derges et al, 2012;Toohey & Rock, 2011). Nevertheless, as exemplified by the killing of dogs in the name of public health, or for the sake of animal welfare, or some combination of these two motivations, the sacrifice of non-human lives may be entailed by both humanist and morethan-human solidarity.…”
Section: Of Rabies and Rescuesmentioning
confidence: 99%